2022
DOI: 10.7150/thno.67036
|View full text |Cite
|
Sign up to set email alerts
|

A hypoxia-responsive supramolecular formulation for imaging-guided photothermal therapy

Abstract: Photothermal agents (PTAs) based on organic small-molecule dyes emerge as promising theranostic strategy in imaging and photothermal therapy (PTT). However, hydrophobicity, photodegradation, and low signal-to-noise ratio impede their transformation from bench to bedside. In this study, a novel supramolecular PTT formulation by a stimuli-responsive macrocyclic host is prepared to overcome these obstacles of organic small-molecule PTAs. Methods: Sulfonated azocalix[4]arene (SAC4A) was syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…[ 7c ] The broad recognition capability of SAC4A promises it as a modular platform capable of delivering other anti‐inflammatory drugs. [ 33 ] We, therefore, evaluated the binding affinities of SAC4A with another four anti‐inflammatory drugs (Figures S30–S33, Supporting Information) widely used in clinic, such as triamcinolone acetonide acetate ((3.8 ± 0.9) × 10 6 m −1 ), dexamethasone ((3.3 ± 0.3) × 10 5 m −1 ), DASA‐58 ((6.0 ± 0.5) × 10 5 m −1 ), and rosiglitazone hydrochloride ((4.2 ± 0.8) × 10 5 m −1 ). Strong binding to these drugs is a prerequisite to reduce the premature dissociation of the complexes when applied to organisms.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7c ] The broad recognition capability of SAC4A promises it as a modular platform capable of delivering other anti‐inflammatory drugs. [ 33 ] We, therefore, evaluated the binding affinities of SAC4A with another four anti‐inflammatory drugs (Figures S30–S33, Supporting Information) widely used in clinic, such as triamcinolone acetonide acetate ((3.8 ± 0.9) × 10 6 m −1 ), dexamethasone ((3.3 ± 0.3) × 10 5 m −1 ), DASA‐58 ((6.0 ± 0.5) × 10 5 m −1 ), and rosiglitazone hydrochloride ((4.2 ± 0.8) × 10 5 m −1 ). Strong binding to these drugs is a prerequisite to reduce the premature dissociation of the complexes when applied to organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Guo et al reported a supramolecular formulation of a hypoxia-responsive calixarene derivative and an IR780 dye for effective imaging-guided PTT. 26 Due to the unique architecture and chemical modification possibilities, calixarene macrocycles have received a lot of attention from the scientific community as agents for coating of AuNPs. The combination with the calixarene skeleton can endow AuNPs with new physicochemical and optical properties crucial for applications ranging from sensing 27,28 to cancer diagnosis and therapy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Normal saline was purchased from Rhawn. SC5A, [ 36 ] SAC4A [ 37 ] and carboxylated azocalix[ n ]arenes (CAC n As, n = 4, 5, 6, 8) [ 38 ] were synthesized and purified according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%